Killer view - Pearson, Ridley (New York : G.P. Putnam's Sons, 2008)
A dead search-and-rescue team member, a missing friend, an unexplained illness at a local water-bottling plant that sends workers to the hospital and sets off biohazard warnings may have something in common as Sun Valley sheriff Walt Fleming follows threads of questionable evidence through the glitter of Sun Valley to expose a masterfully planned domestic terrorist attack.
Map on endpaper.
Keywords: Sheriffs -- Fiction; Fleming, Walt (Fictitious character) -- Fiction; Sun Valley (Idaho) -- Fiction